POLICY GAP ANALYSIS: ENHANCING PUBLIC AGENCIES FOR RENEWABLE ENERGY TRANSITION (STUDY CASE: BMKG’S GOVERNMENT PERFORMANCE ACCOUNTABILITY FOR METEOROLOGY INFORMATION) - Supandi, Achmad (Pusdiklat BMKG, 2022)
Research on gap analysis of policy implementation is a sub-grand theory from policy implementation very rarely reviewed in journals. This study focuses on the Gap Analysis of Government Performance Accountability (GPA) for optimizing performance management of Meteorology information services in the Indonesian Meteorology, Climatology and Geophysics Agency (BMKG) to support the improvement of the renewable energy transition. This research uses a qualitative method through Creswell’s spiral analysis approach and data processing using NVIVO12 software. based on the results of the study it was found that conventional weather information needs to be upgraded to thematic information to support the improvement of renewable energy transition so that it can be operationalized by public agencies such as the state electricity company (PLN) and other SOEs from water energy resources and solar energy.